FUNGSI PENGGUNAAN ALIH KODE DALAM CERAMAH GUS IQDAM: KAJIAN SOSIOLINGUISTIK - Khoironi, Haris (Universitas Sebelas Maret, 2024)
In communication, language serves as the primary tool used. Each individual has uniqueness in language usage, one of which is through the use of linguistic aspects such as code-mixing and code-switching. This study aims to describe the forms of code-switching found in Gus Iqdam's lecture and the purposes of code-switching. This research uses a qualitative descriptive method. The data used are speeches containing code-switching obtained from the YouTube video 'GUS IQDAM & SOIMAH SAMPAI MENANGIS JAMAAH RADIUS 10 KM // PENDOPO TULUNGO BANTUL // 24 NOVEMBER 2023'. Data collection techniques in this study use a listening approach with the application of advanced techniques of listening with free talk involvement and note-taking techniques through orthographic transcription. Data analysis in this study adopts Spradley's method, namely domain analysis and taxonomic analysis. In the lecture video, several types of code-switching were found, namely internal code-switching and external code-switching. The use of code-switching is generally done, among others, for the purpose of familiarizing the atmosphere, respecting the interlocutor, convincing the topic of conversation, evoking humor, and simply styling or prestige. Keywords: code-switching, sociolinguistics, lecture, gus iqdam